MORPHOLOGICAL FEATURES OF LIVER CANCER ON THE BACKGROUND OF VIRAL GENESIS’ CIRRHOSIS - Gavryluk, A.A.; Tumanskiy, V.A.; Moroz, L.V. (World of Medicine and Biology, 2012)
A retrospective analysis was conducted of clinical data on 444 patients with chronic viral hepatitis B, C and B + C who underwent liver biopsy. By the results of clinical and morphological studies of cirrhosis of the liver, cancer was developed in 12,28 % of patients with chronic viral hepatitis (in 71,4 % of cases against a background of chronic viral hepatitis C, 28,5 % of cases against a background of chronic viral hepatitis B). Conducted histopathological and histochemical studies made it possible to identify the microscopic characteristic of liver cancer, which have arisen in patients with chronic viral hepatitis B and C on the background of liver cirrhosis and to identify dysplastic changes in the liver, which are observed in the perifocal zone of liver cancer, and that can be observed at cirrhosis of the liver, as possible predictors of cancer.